Simulation Study of Carbon Extraction from Coal Gasification Fine Slag by Airflow Classification Based on CFD-DEM - LI Xiangyang; ZHANG Qian; LI Le; BAI Hui; HUANG Wei (Taiyuan Ligong Daxue xuebao)
[Purposes] The separation of carbon form coal gasification slag is an important means to realize its reduction, harmlessness, and resource utilization. The airflow classification method has unique advantages because of its ability to efficiently process fine-graded particles without waste water and exhaust gas emmission. [Methods] According to CFD-DEM simulation, the gas-solid flow characteristics of horizontal turbine air classifier were investigated, and the matching relationship between the air inlet direction and turbine steering was explored. The flow mechanism of carbon and ash particles was clarified. On this basis, the air inlet direction in the turbine air classifier was optimized, and the effects of inlet air velocity and turbine speed on the efficient carbon extraction for gasification slag in air classifier were predicted. [Findings] The results show that the inlet direction of the turbine air classifier has a significant effect on the flow field distribution and the efficiency of carbon extraction for gasification slag. The tangential air inlet leads to the generation of secondary vortices in the grading zone and elution zone that interfere with each other, affecting the separation efficiency of carbon and ash particles. The optimization of tangential air inlet to vertical upward avoids the mutual interference between the elution zone and the classification zone. The secondary vortex between the turbine and the blades is eliminated. The uniform distribution of the flow field in the classification zone is improved and stabilized. The efficiency of carbon extraction is increased. In the optimized turbine airflow classifier, by matching the inlet air velocity with the turbine speed, the carbon content in the carbon-rich product can reach 80.95%, and the carbon recovery rate can reach 59.83%.